ANALISIS KEMAMPUAN KOMUNIKASI MATEMATIS SISWA SMP PADA MATERI PERSAMAAN GARIS LURUS: KELAS REGULER DAN KELAS TAHFIDZ (Asimtot : Jurnal Kependidikan Matematika, 2025)
This study aims to analyze the mathematical communication skills of junior high school students on straight line equation material based on regular classes and tahfidz classes. The approach used is descriptive quantitative with survey and test methods. The subjects of this study were 23 8th grade students consisting of 12 regular class students and 11 tahfidz class students in one of the junior high schools in Central Java. The data collection instruments used include tests, with 3 description questions that represent indicators of mathematical communication skills. The data processing technique used is the analysis of mathematical communication skills related to straight line equation material, in terms of regular classes and memorized classes based on each indicator. Based on the analysis, the average score of regular class students is 54.7% while tahfidz class students is 75.8%. With this difference, it can be concluded that the mathematical communication skills of tahfidz class students are higher than those of regular class students.